2015
DOI: 10.5206/cjsotl-rcacea.2015.3.2
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Assessment of ‘None of the Above’ on Multiple Choice Tests in a First Year Psychology Classroom

Abstract: Multiple choice writing guidelines are decidedly split on the use of ‘none of the above’ (NOTA), with some authors discouraging and others advocating its use. Moreover, empirical studies of NOTA have produced mixed results. Generally, these studies have utilized NOTA as either the correct response or a distractor and assessed its effect on difficulty and discrimination. In these studies, NOTA commonly yields increased difficulty when it is used as the correct response, and no change in discrimination regardles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 41 publications
(57 reference statements)
3
12
0
Order By: Relevance
“…(Haladyna et al, 2002, Tarrant et al, 2006a, 2006b Use of none of the above The use of "none of the above" means that students may correctly eliminate this option by identifying at least one other response as being correct. (Haladyna et al, 2002, Pachai et al, 2015, Tarrant et al, 2006a, 2006b Option order / position of the correct option…”
Section: Sampling Strategy and Data Collectionmentioning
confidence: 99%
“…(Haladyna et al, 2002, Tarrant et al, 2006a, 2006b Use of none of the above The use of "none of the above" means that students may correctly eliminate this option by identifying at least one other response as being correct. (Haladyna et al, 2002, Pachai et al, 2015, Tarrant et al, 2006a, 2006b Option order / position of the correct option…”
Section: Sampling Strategy and Data Collectionmentioning
confidence: 99%
“…To add to the effective role of selective (multiple-choice) mode of test practice manipulation, Pachai, DiBattista, and Kim (2015) showed that when using a multiple-choice test for the purpose of instructional practice in learning contexts, a successful differentiation is made among students based on how well they know the material being tested and instructed. In practice, the arguing point, according to Little, Bjork, Bjork, and Angello (2012) is that the manipulation of this norm of test practice not only challenges learners but also allows them to succeed and have required results when they have the requisite knowledge, ideally culminating in a range of performance with a relatively high average.…”
Section: Discussionmentioning
confidence: 99%
“…(4) One tempting way to increase the number of distractors in an MC item is to include "all of the above" (AOTA) or "none of the above" (NOTA) as a response option. However, most experts agree that these "inclusive" response options should only be used with caution-or never at all (Harasym, Leong, Violato, Brant, & Lorscheider, 1998;Pachai, DiBattista, & Kim, 2015;Ibbett & Wheldon, 2016;Rush et al, 2016). On the one hand, MC Items with inclusive response options are prone to misreading by students.…”
Section: Recommendations For Classroom Teachersmentioning
confidence: 99%